AN ANALYSIS OF STUDENT SPEAKING FLUENCY THROUGH YOUTUBE PODCAST - Baramarta, Ajeng; Barotun Mabaroh; Yenni Rachman Wiji Lestari (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
This study aims to explore the influence of YouTube podcasts in the students' speaking fluency. The problem in this study is the fluency of the students to speak by using Podcast. Based on the issues above, this research purpose to analyze YouTube podcasts contribute to these fluency-related skills and analyze the platform as a learning tool. This research is qualitative descriptive with the researcher as the primary human instrument for data collection. The subject in this study is XII-7 grade of SMA Negeri 2 Kota Pasuruan in academic year 2024/2025. The total number is 34 students. The data are collected by observation. The findings reveal varying levels of fluency improvement: high-performing students exhibited coherent speech with occasional pauses, while medium-performing students faced challenges with pronunciation and consistent fluency. Low-performing students struggled with frequent hesitations and fragmented sentences. The study underscores the potential of YouTube podcasts to facilitate fluency by providing authentic language exposure and encouraging self-directed practice.